PERTUMBUHAN BIBIT JERUK SIAM HASIL OKULASI PADA BERBAGAI KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK ORGANIK CAIR: Growth of Siamese Orange Seedlings from Grafting on Various Compositions of Planting Media and Liquid Organic Fertilizers - Ghazali, Zahra Zalirah; Nursaman, Herman; Ratih (Fakultas Pertanian Universitas Islam Makassar, 2025)
Jeruk siam (Citrus nobilis L.) is one of the most popular horticultural commodities in Indonesia. The growth quality of citrus seedlings is strongly influenced by the composition of the growing media and the appropriate dosage of fertilizer. This study aimed to determine the effect of growing media composition and liquid organic fertilizer dosage on the growth of grafted Citrus nobilis seedlings. The research was conducted from January to April 2025 using a factorial Randomized Complete Block Design (RCBD) with two factors. The first factor was the growing media composition (soil, manure, husk), consisting of K1 = 1:1:1, K2 = 2:1:1, and K3 = 2:2:1. The second factor was the dosage of liquid organic fertilizer: P1 = 10 ml/l, P2 = 15 ml/l, and P3 = 20 ml/l. The results showed that the growing media composition of soil : manure : husk with aratio of 2:1:1 (K2) gave the best growth performance, with an average plant height of 47.44 cm, 23 leaves, stem diameter of 0.63 cm, and root volume of 16.00 ml at 10 weeks after planting. The 15 ml/l dosage of liquid organic fertilizer (P2) also promoted optimal growth with results close to the best media treatment. No significant interaction was found between the media composition and fertilizer dosage on the growth of the grafted Citrus nobilis seedlings.